2011
DOI: 10.2166/wst.2011.501
|View full text |Cite
|
Sign up to set email alerts
|

Determination of toxic heavy metals in sea water by FAAS after preconcentration with a novel chelating resin

Abstract: A solid phase extraction procedure was developed for preconcentration of toxic heavy metals such as cadmium, cobalt, copper, manganese, lead and zinc in sea water samples. A microcolumn packed with 6-[(4-hydroxyphenyl)diazenyl]naphthalene-2,3-diol-formaldehyde (HPDN-F) resin acts as a sorbent to retain the analyte ions by forming metal chelates. The retained trace level metal was subsequently eluted with 1 mol/L HCl and the acid eluent was analysed by Flame Atomic Absorption Spectrophotometer (FAAS). The HPDN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Over the past several decades, the development of highly effective analytical methods, such as inductively coupled plasma atomic emission spectroscopy (ICP-AES), 7 atomic uo-rescence spectrometry, 8 atomic absorption spectrometry (AAS), 7 colourimetric analysis, 9 inductively coupled plasma mass spectrometry (ICP-MS) 10,11 and ultraviolet-visible (UV-vis) spectrometry, 12,13 for the determination of toxic heavy metals (HMs) at trace levels has attracted increasing interest. Although these methods are sensitive for the determination of HMs at trace levels, long analysis times and tedious sample preparation methods are needed to meet requirements for real sample analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, the development of highly effective analytical methods, such as inductively coupled plasma atomic emission spectroscopy (ICP-AES), 7 atomic uo-rescence spectrometry, 8 atomic absorption spectrometry (AAS), 7 colourimetric analysis, 9 inductively coupled plasma mass spectrometry (ICP-MS) 10,11 and ultraviolet-visible (UV-vis) spectrometry, 12,13 for the determination of toxic heavy metals (HMs) at trace levels has attracted increasing interest. Although these methods are sensitive for the determination of HMs at trace levels, long analysis times and tedious sample preparation methods are needed to meet requirements for real sample analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, determination of Pb 2+ in coastal waters is of great importance for the environmental protection and public health. Many techniques have been developed for the determination of heavy metal ions, including atomic absorption spectroscopy, atomic emission spectroscopy, and inductively coupled plasma-mass spectrometry (Manivannan and Biju, 2011;Zhu et al, 2017). Although these methods possess various advantages and have been commonly used, the requirement of cumbersome instruments, time-consuming pretreatments, and high cost are the inevitable limitations (Hu et al, 2015;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…With the tremendous increase in the industrial use of heavy metals, seawater pollution has become a severe problem. 1 Metallic substances can be ingested by sh and accumulate in vital organs at high levels, as some studies 2 have shown. The toxicity of Cd(II) is well known; 3 it easily enters the human body through the food chain 4 and can cause severe organ damage.…”
Section: Introductionmentioning
confidence: 99%